Directions of Digital Technologies Development in the Supply Chain Management of the Russian Economy - A.V. Kolesnikov; I.V. Orlova; E.Yu. Kamchatova; L.O. Babeshko; Serebrennikova Serebrennikova (International Journal of Supply Chain Management, 2020)
Abstract— The main objective of this paper is to investigate the digitalization and technologies impact on supply chain management of agricultural industry.  This paper provides practical examples of supply chain digitalization, as well as its socio-economic and environmental effects. The absence of processes that are compatible with the high production requirements adopted in foreign markets can lead to crisis phenomena in domestic industries with high potential and rapid growth dynamics in agriculture industry. Agriculture in Russia is an integral part of the agro-industrial complex, and the program “Digitalization of its supply chain” should provide participants with the opportunity to use broadband, mobile, LPWAN communications, information technologies (small and big data, management platforms, etc.) of the domestic instrument industry (tags, controllers, sensors, control units) to improve significantly the efficiency of agriculture. The opportunities for modernizing the industry are huge. Food security of the country and the development of export potential, turn agriculture into a high-tech industry that can not only provide food for itself, but also many countries of the world through the global supply chain system, as well as create opportunities for the introduction of new innovative developments that have not exist before, stimulate management decisions that can provide the population with high-quality and safe products. According to expert estimates, during the season, the farmer has to make more than 40 different decisions in limited time intervals. Many of these solutions, which affect directly the production economy, are objects of digitalization in supply chain.